Assessment of an anti-scale low-frequency electromagnetic field device on drinking water biofilms. Issue 9 (21st October 2018) - Gosselin, F.; Mathieu, L.; Block, J.-C.; Carteret, C.; Muhr, H.; Jorand, F. P. A.
Abstract: Low intensity and very low-frequency electromagnetic fields (EMF) used for preventing scaling in water distribution systems were tested for the first time for their potential impact on drinking water biofilms. The assays were carried out in laboratory-scale flow-through reactors that mimic water distribution systems. The drinking water biofilms were not directly exposed to the core of the EMF generator and only subjected to waterborne electromagnetic waves. The density and chlorine susceptibility of nascent or mature biofilms grown under exposure to EMF were evaluated in soft and hard water. This EMF treatment was able to modify CaCO3 crystallization but it did not significantly affect biofilms. Indeed, over all the tested conditions, there was no significant change in cell number, or in the integrity of the cells (membrane, culturability), and no measurable effect of chlorine on the biofilm.